PERSEPSI MASYARAKAT TERHADAP EFEKTIVITAS PELAYANAN PEMBAYARAN PAJAK BERMOTOR BERBASIS DIGITAL DIKABUPATEN SERANG - Rico, Rico Sandi Aji; Munawaroh Munawaroh (Kampus Akademik Publiser, 2025)
Public services are one of the main tasks of the government in an effort to meet the needs of the community, so it is the government's duty to provide the best service, because many people complain about very complicated procedures, complicated services and the lack of certainty regarding tax payment times. So the government is preparing digital-based tax payments because it can help people when they want to pay taxes